INDUSTRIAL REVOLUTION 4.0: AND THE IMPACT ON HUMAN RESOURCES - Nova Jayanti Harahap; Mulya Rafika (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2020)
Indonesia began to face the Industrial 4.0 era, where all systems began to be connected digitally. This condition is inseparable from the rapid development of industrial scientific knowledge. Through a literature study, this paper aims to look at the data quality approach regarding how the emergence of Industry 4.0 is related to the development of industrial engineering science, what challenges are faced and how the government should direct the development of industry 4.0. The results of this study indicate that in its development, the 4.0 industrial revolution had an influence on human resources to evolve to the emergence of the idea of Industry 4.0. The idea brought the concept of combining digital technology and the internet with conventional industry which ultimately aims to increase productivity, efficiency and reduce the number of unemployed significantly. However, aside from that, some of the consequences faced are related to the negative impacts of Industry 4.0 in which impacts on human resources. This is where various challenges arise for the government. There are many roles that the government can play to face the challenges of the emergence of Industry 4.0. The main role is to focus on equipping human resources by expanding employment and also providing opportunities to be able to open entrepreneurship in various business places such as, in individual business centers and in the vicinity of franchise businesses.